2014
DOI: 10.1007/s00467-014-2982-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of medication-related problems in children with kidney disease

Abstract: BackgroundMedication-related problems (MRPs) are the undesirable effects of pharmacotherapy that can potentially lead to harm. The epidemiology of MRPs in paediatric renal patients is unknown. We aimed to characterise MRPs in this population at two tertiary care hospitals in the UK.MethodsPrescription charts for children (≤18 years) were reviewed to identify MRPs, and characterised using a specific proforma with a standard operational definition. MRP predictors were evaluated by logistic regression and severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
6
12
2
Order By: Relevance
“…This result was higher than what has been found in international and Brazilian studies conducted in general pediatrics, in which DRP ranged from 20 to 70%. [16][17][18][19][20][21] The result, however, is lower than what was observed in the study by Sabry et al, 11 in which all 60 cardiopathic children evaluated were exposed to DRP while in an Egyptian hospital. However, it is worth noting that local specificities, population characteristics, methods of identification and classification of DRPs and the follow-up time of the study make these comparisons difficult.…”
Section: Characteristics Valuecontrasting
confidence: 63%
See 2 more Smart Citations
“…This result was higher than what has been found in international and Brazilian studies conducted in general pediatrics, in which DRP ranged from 20 to 70%. [16][17][18][19][20][21] The result, however, is lower than what was observed in the study by Sabry et al, 11 in which all 60 cardiopathic children evaluated were exposed to DRP while in an Egyptian hospital. However, it is worth noting that local specificities, population characteristics, methods of identification and classification of DRPs and the follow-up time of the study make these comparisons difficult.…”
Section: Characteristics Valuecontrasting
confidence: 63%
“…22,23 Similar to pediatric studies, antimicrobials were the group of drugs most involved in GRP. [16][17][18][19][20]24,25 Some authors state that the risk of adverse events related to each drug is directly associated with the frequency of prescription. 24,25 However, similar to the findings of Blix et al, 26 in our study the most involved medications were not necessarily the most prescribed, showing that the risk of damage is related to the chemical and pharmacological characteristics of the medications, as well as patient characteristics.…”
Section: Characteristics Valuementioning
confidence: 99%
See 1 more Smart Citation
“…In the present study (27.52%) of the DTPs was found to be dose too low. This was in line with a study done in London (21.7%), Canada (19%) and Egypt (21.09%) (25,29,45). Dose too high was found to be (10.95%) in the present study which was lower than the study done in Hong Kong 19.3% (22).…”
Section: Discussionsupporting
confidence: 90%
“…Other findings also reported that DTPs were more frequent in males than in female. But, it was statistically insignificant (22,35,45). This indicated that drug therapy problems could be occurred irrespective of the sex.…”
Section: Discussionmentioning
confidence: 93%